Knowledge, Representation and Communication of the Military Landscape of Sardinia During the Second World War (diségno, 2024)
A mastery in the use of tools, methods, and graphic techniques essential for a thorough understanding and representation of cultural heritage has traditionally been recognized in the field of Drawing. Today, this capability is enhanced by the development of digital technologies which, when combined with the latest surveying systems, contribute to the creation of high-value scientific interoperable digital databases. However, beyond the necessity of detailed data acquisition, significant importance is also placed on the communication of architectural and landscape heritage, which distinguishes the various forms of historical settlements. Expressing and sharing the results and findings of these investigations play a fundamental role in raising awareness among those who inhabit these places and are part of them. This process fosters a ‘new’ sensitivity, an important goal for ensuring the protection of endangered heritage and an essential contribution to preserving its memory. In this respect, the landscape of the 20th-century wars in Sardinia serves as a significant example that is common to the coasts of the Western Mediterranean. It characterizes the urban contexts of Cagliari and La Maddalena and, to a lesser extent, the entire region.
Keywords: survey; representation; communication; historical military landscape; Sardinia